Effect of melatonin on tumor growth and angiogenesis in xenograft model of breast cancer - Jardim-Perassi, Bruna Victorasso [UNESP]; Arbab, Ali S.; Ferreira, Livia Carvalho [UNESP]; Borin, Thaiz Ferraz; Varma, Nadimpalli R. S.; Iskander, A. S. M.; Shankar, Adarsh; Ali, Meser M.; Pires de Campos Zuccari, Debora Aparecida (Public Library Science, 2014)
As neovascularization is essential for tumor growth and metastasis, controlling angiogenesis is a promising tactic in limiting cancer progression. Melatonin has been studied for their inhibitory properties on angiogenesis in cancer. We performed an in vivo study to evaluate the effects of melatonin treatment on angiogenesis in breast cancer. Cell viability was measured by MTT assay after melatonin treatment in triple-negative breast cancer cells (MDA-MB-231). After, cells were implanted in athymic nude mice and treated with melatonin or vehicle daily, administered intraperitoneally 1 hour before turning the room light off. Volume of the tumors was measured weekly with a digital caliper and at the end of treatments animals underwent single photon emission computed tomography (SPECT) with Technetium-99m tagged vascular endothelial growth factor (VEGF) C to detect in vivo angiogenesis. In addition, expression of pro-angiogenic/growth factors in the tumor extracts was evaluated by membrane antibody array and collected tumor tissues were analyzed with histochemical staining. Melatonin in vitro treatment (1 mM) decreased cell viability (p<0.05). The breast cancer xenografts nude mice treated with melatonin showed reduced tumor size and cell proliferation (Ki-67) compared to control animals after 21 days of treatment (p<0.05). Expression of VEGF receptor 2 decreased significantly in the treated animals compared to that of control when determined by immunohistochemistry (p<0.05) but the changes were not significant on SPECT (p>0.05) images. In addition, there was a decrease of micro-vessel density (Von Willebrand Factor) in melatonin treated mice (p<0.05). However, semiquantitative densitometry analysis of membrane array indicated increased expression of epidermal growth factor receptor and insulin-like growth factor 1 in treated tumors compared to vehicle treated tumors (p<0.05). In conclusion, melatonin treatment showed effectiveness in reducing tumor growth and cell proliferation, as well as in the inhibition of angiogenesis.